2003
DOI: 10.21000/jasmr03011206
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Organic Carbon in Reclaimed Surface Coal Mine Soils of Wyoming

Abstract: Abstract. The potential to sequester carbon and increase organic nutrient storage in disturbed soils, such as those reclaimed after surface coal mining, appears to be significant. Quantification of organic carbon accumulation is complicated, however, by the presence of coal and coal dust in these soils. Our preliminary data on organic matter content of reclaimed soils at surface coal mines in Wyoming suggest they are sequestering carbon at a rapid rate. Data from a surface mine reclamation site near Hanna, WY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…Therefore, SOC accumulates Table 2 Texture, bulk density, pH, electrical conductivity and C to N ratio of forest and grass age chronosequunce sites, Ohio. rapidly in reclaimed soils (Stahl et al, 2003), which can recover structurally towards a native soil condition after a period of 10-15 years . Similarly, ecosystem N pool increased at a mean rate of 145 kg ha − 1 yr − 1 (with a range of 77 to 183 kg ha − 1 yr − 1 ) in forest and 45 kg ha −1 yr −1 (with a range of 2 to 82 kg ha −1 yr −1 ) in pasture (Fig.…”
Section: Rate Of Carbon and Nitrogen Sequestration In Terrestrial Ecomentioning
confidence: 99%
“…Therefore, SOC accumulates Table 2 Texture, bulk density, pH, electrical conductivity and C to N ratio of forest and grass age chronosequunce sites, Ohio. rapidly in reclaimed soils (Stahl et al, 2003), which can recover structurally towards a native soil condition after a period of 10-15 years . Similarly, ecosystem N pool increased at a mean rate of 145 kg ha − 1 yr − 1 (with a range of 77 to 183 kg ha − 1 yr − 1 ) in forest and 45 kg ha −1 yr −1 (with a range of 2 to 82 kg ha −1 yr −1 ) in pasture (Fig.…”
Section: Rate Of Carbon and Nitrogen Sequestration In Terrestrial Ecomentioning
confidence: 99%
“…Mine land or overburden spoil being deficient in carbon offers potential for large storage of organic carbon. Stahl et al (2003) estimated that carbon accumulations on mine soils were greater than in native sites in Wyoming, USA. Burger and Zipper (2002) also found that forest planted on mine land could be more productive than native forest before mining.…”
Section: Reclaimed Site Observationsmentioning
confidence: 99%
“…The moderate disturbance of soil caused by agricultural tillage has resulted in significant losses of SOC in cultivated soils throughout the world. Loss of SOC or SOM has been commonly reported for soils disturbed by activities associated with surface mining (Visser et al, 1984;Harris et al, 1993;Stahl et al, 2002) Reclamation of disturbed and degraded soils generally leads to redevelopment of SOM in the form of plant, microbial and animal residues (Stahl et al, 2003), which greatly contributes to improvement of soil fertility as well as soil structure, water holding capacity, biotic activity, and plant growth (Harris et al, 1996;Lal et al, 1998). Reestablishment of soil carbon pools in disturbed soil also sequesters carbon from the atmosphere where it is contributing to global climate change.…”
Section: Introductionmentioning
confidence: 99%